2003
DOI: 10.1186/1471-2458-3-21
|View full text |Cite
|
Sign up to set email alerts
|

The influence of calcium and magnesium in drinking water and diet on cardiovascular risk factors in individuals living in hard and soft water areas with differences in cardiovascular mortality

Abstract: BackgroundThe role of water hardness as a risk factor for cardiovascular disease has been widely investigated and evaluated as regards regional differences in cardiovascular disease. This study was performed to evaluate the relation between calcium and magnesium in drinking water and diet and risk factors for cardiovascular disease in individuals living in hard and soft water areas with considerable differences in cardiovascular mortality.MethodsA random sample of 207 individuals living in two municipalities c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
2
59
0
Order By: Relevance
“…This extreme scarcity of Ca and Mg can produce several diseases in populations which use this water for drinking and cooking purposes. Epidemiologic studies in Sweden (Nerbrand et al, 2003), Finland (Kousa et al, 2006) and Taiwan (Yang et al, 2006), where the minimum values found for Ca and Mg levels were much higher than the values found in our study (average of 12.5 mg/l for Ca and 3.3 mg/l for Mg in Sweden; 4.39 mg/l for Ca and 1.00 mg/l for Mg in Finland; minimum value of 25.1 mg/l for Ca in Taiwan), have shown a protective effect of Ca and/or Mg from drinking water on the risk of death from cardiovascular diseases. Statistical studies carried out in Taiwan (Yang, 1998) and Spain (Ferrándiz et al, 2004) have demonstrated the protective effect of Ca and/or Mg in drinking water against cerebrovascular mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extreme scarcity of Ca and Mg can produce several diseases in populations which use this water for drinking and cooking purposes. Epidemiologic studies in Sweden (Nerbrand et al, 2003), Finland (Kousa et al, 2006) and Taiwan (Yang et al, 2006), where the minimum values found for Ca and Mg levels were much higher than the values found in our study (average of 12.5 mg/l for Ca and 3.3 mg/l for Mg in Sweden; 4.39 mg/l for Ca and 1.00 mg/l for Mg in Finland; minimum value of 25.1 mg/l for Ca in Taiwan), have shown a protective effect of Ca and/or Mg from drinking water on the risk of death from cardiovascular diseases. Statistical studies carried out in Taiwan (Yang, 1998) and Spain (Ferrándiz et al, 2004) have demonstrated the protective effect of Ca and/or Mg in drinking water against cerebrovascular mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The scarcity of some base cations as calcium and magnesium in drinking water has been associated with cardiovascular diseases (Nerbrand et al, 2003;Kousa et al, 2006;Yang et al, 2006). In Spain, an increased death rate from cardiovascular and cerebrovascular diseases was reported in areas supplied with soft drinking water (Ferrándiz et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies have demonstrated the same relationships, one of the last being a study from Finland in 2004 [2] and reviews have been presented [3,4]. Other studies have, however, not found such relationships or only weak associations between mineral intake and risk for cardiovascular disease [5,6]. This discrepancy may be due to an absence of causality or to variations in the populations studied regarding intake of minerals.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies have documented that softer water is associated with higher CVD death rates; this protective role is suggested to be because of the water Ca content [28, 29]. …”
Section: Discussionmentioning
confidence: 99%